Activated Circulating T Follicular Helper Cells Are Associated with Disease Severity in Patients with Psoriasis. (28th September 2016) - Wang, Ying; Wang, Lili; Yang, Haoyu; Yuan, Weichang; Ren, Jingyi; Bai, Yanping
Abstract : Circulating T follicular helper (cTfh) cells are known to be involved in numerous immune-mediated diseases, but their pathological role in psoriasis is less fully investigated. Herein, we aimed to identify whether cTfh cells contributed to the pathogenesis of psoriasis. The frequency and function of cTfh cells were compared between patients with psoriasis vulgaris and healthy controls, and the infiltration of Tfh cells was detected between lesional and nonlesional skin tissues of psoriasis patients. Moreover, the dynamic change of cTfh cells before and after acitretin treatment was evaluated. Our results showed both increased frequency and activation (indicated by higher expression of ICOS, PD-1, HLA-DR, and Ki-67 and increased production of IL-21, IL-17, and IFN- γ ) of cTfh cells in psoriasis patients. Compared with nonlesional skin tissues of psoriasis patients, the number of infiltrated Tfh cells was significantly increased in psoriasis lesions. In addition, positive correlations between the percentage of cTfh, functional markers on cTfh cells in peripheral blood and disease severity were noted. Furthermore, the frequency of cTfh cells and the levels of cytokines secreted by cTfh cells were all significantly decreased after 1-month treatment.